Thermoplastic resin composite material with excellent mechanical property and preparation method thereof

By introducing 1,5-naphthalene diisocyanate into the thermoplastic resin and carrying out grafting reaction, the thermoplastic resin-g-NDI was prepared and mixed with mineral fillers and antioxidants, the problem of insufficient mechanical properties of the thermoplastic resin composite was solved, and significant improvement in mechanical properties was achieved.

CN119529416AInactive Publication Date: 2025-02-28HEFEI GENIUS NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311087589.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The application of existing thermoplastic resin composites in automotive interiors and other fields is limited by mechanical properties, especially in poor performance when withstanding weight and impact.

Method used

By introducing 1,5-naphthalene diisocyanate (NDI) into the thermoplastic resin and carrying out grafting reaction, the thermoplastic resin -g-NDI was prepared and mixed with mineral fillers and antioxidants to form a high-performance thermoplastic resin composite material.

Benefits of technology

It significantly improves the mechanical properties of thermoplastic resins, improves the compatibility between resins and mineral fillers, and improves the tensile strength, bending strength and impact toughness of composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure FDA0004416581480000011
    Figure FDA0004416581480000011
Patent Text Reader

Abstract

The invention discloses a thermoplastic resin composite material with excellent mechanical properties and a preparation method thereof. The thermoplastic resin composite material is prepared from the following components in parts by weight: 90 to 110 parts of thermoplastic resin, 10 to 16 parts of mineral filler, 0.2 to 0.4 part of thermoplastic resin-g-NDI and 0.1 to 0.5 part of antioxidant. The invention also discloses a preparation method of the thermoplastic resin composite material. According to the thermoplastic resin-g-NDI, an isocyanato functional group is introduced into thermoplastic resin through a grafting reaction, the compatibility between the thermoplastic resin and mineral filler can be improved, and compared with a compatilizer SEBS-g-MAH commonly used in the current market, the grafting rate is higher, and the compatibility between the thermoplastic resin-g-NDI and mineral filler is improved. And the compatibility between the thermoplastic resin and the mineral filler is better. Therefore, the prepared thermoplastic resin composite material has excellent mechanical properties, can be used in the field of automobile household appliance materials, and has excellent application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to a thermoplastic resin composite material with excellent mechanical properties and a preparation method thereof. Background Art

[0002] Thermoplastic resin is a widely used polymer polyester resin, including: PE-polyethylene, PP-polypropylene, PVC-polyvinyl chloride, PS-polystyrene, PA-polyamide, POM-polyoxymethylene, PC-polycarbonate, polyphenylene ether, polysulfone, rubber, etc. Thermoplastic resin has the advantages of good fatigue resistance, good heat resistance and excellent dimensional stability, but its heat resistance and rigidity are poor, especially in some specific automotive interior material application fields, the mechanical properties of thermoplastic resin are very high, which limits the application of thermoplastic resin composites in some specific fields.

[0003] At present, the requirements for automobile weight reduction and energy saving require that thermoplastic resins are used in automobile interiors such as seats, steering wheels, instrument panels, door panels, etc. However, since they are used in automobiles, they are required to have sufficient strength and rigidity. Components such as seats, door panels, and instrument panels must not only be able to withstand the weight of passengers, switch operations, and other forces, but also maintain structural stability and shape stability. At the same time, they also need to have a certain impact toughness to absorb energy and reduce damage when impacted or collided. For example, storage compartments, center consoles, and other components in the car need to have a certain impact toughness to protect passengers and the interior materials themselves. At present, the mechanical properties of the resin are mainly improved by adding fillers, but due to the poor compatibility between fillers and thermoplastic resins, agglomeration is easy to occur, thus affecting other properties of thermoplastic resins. At present, there are also methods of adding compatibilizers such as SEBS-g-MAH, but satisfactory mechanical properties have not yet been achieved.

[0004] In view of these deficiencies, the present invention innovatively synthesizes a new type of high-performance thermoplastic resin composite material, which has excellent mechanical properties. This thermoplastic resin composite material has not been reported so far, which has very important practical significance for expanding the application field of thermoplastic resin composite materials. Summary of the invention

[0005] In view of this, the present invention innovatively synthesizes a thermoplastic resin composite material with excellent mechanical properties, which has good mechanical properties and solves the technical problem of limited mechanical properties of thermoplastic resins in the prior art.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] A thermoplastic resin composite material with excellent mechanical properties and a preparation method thereof, which comprises the following components in parts by weight:

[0008]

[0009] The mineral filler is one of talcum powder, calcium carbonate, mica powder, wollastonite and barium sulfate.

[0010] The thermoplastic resin in the above-mentioned base thermoplastic resin and the "thermoplastic resin-g-NDI" is one of polyethylene (PE), polypropylene (PP), polystyrene (PS), polybutylene terephthalate (PBT), and polyamide 6 (PA6).

[0011] The preparation method of the thermoplastic resin-g-NDI comprises the following steps:

[0012] (1) Weighing a certain amount of thermoplastic resin, 1,5-naphthalene diisocyanate (NDI), and initiator, mixing and stirring uniformly to obtain a mixture;

[0013] (2) Extruding the mixture obtained in step (1) from an extruder and granulating it to obtain a thermoplastic resin grafted with 1,5-naphthalene diisocyanate, namely, a thermoplastic resin-g-NDI.

[0014] Preferably, the mass ratio of the thermoplastic resin, 1,5-naphthalene diisocyanate (NDI) and the initiator in step (1) is (40-50):(16-20):(0.1-0.3).

[0015] The initiator is azobisisobutyronitrile, sodium persulfate, benzoyl peroxide or azobisisobutyronitrile.

[0016] The antioxidant is one of BASF's tris(2,4-di-tert-butyl)phenyl phosphite (referred to as Irganox 168), tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester (referred to as Irganox 1010) and N,N'-hexane-1,6-diylbis(3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide)) (Irganox 1098) or a mixture of several thereof.

[0017] The high-performance thermoplastic resin composite material and the preparation method thereof comprise the following steps:

[0018] (1) Weigh 80-100 parts of a thermoplastic resin, 10-16 parts of a mineral filler, 0.2-0.4 parts of a thermoplastic resin-g-NDI, and 0.1-0.5 parts of an antioxidant, mix and stir to obtain a mixture;

[0019] (2) Extruding the mixed material obtained in step (1) from an extruder and granulating it to obtain a thermoplastic resin composite material.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The thermoplastic resin-g-NDI prepared by the present invention can significantly improve the mechanical properties of the thermoplastic resin. The isocyanate functional group is introduced into the thermoplastic resin through a grafting reaction, so that the compatibility between the thermoplastic resin and the mineral filler can be improved. Compared with the commonly used compatibilizer SEBS-g-MAH on the market, the grafting rate of the thermoplastic resin-g-NDI is higher, the compatibility between the thermoplastic resin and the mineral filler is better, and the mechanical properties of the thermoplastic resin improved by using it are higher.

[0022] The thermoplastic resin composite material prepared by the invention has excellent mechanical properties and can be used in the field of automobile and household appliance materials, and has excellent application prospects. DETAILED DESCRIPTION

[0023] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0025] The raw materials used in the following examples are as follows:

[0026] PBT (model 2002U), Polyplastics, Japan;

[0027] PP (model Z30S), Maoming Petrochemical;

[0028] PE (model 5070), Panjin ethylene;

[0029] PA6 (model CM1017), Toray, Japan; PS (model 350), Guoqiao, Taiwan, China;

[0030] SEBS-g-MAH, Nanjing Deba Polymer Materials Co., Ltd.;

[0031] 1,5-Naphthalene diisocyanate, Hubei Kewode Chemical Co., Ltd.;

[0032] Azobis(2-isoheptanonitrile), Guangdong Wengjiang Chemical Reagent Co., Ltd.;

[0033] Calcium carbonate, Shandong Jinzhao Chemical Co., Ltd.;

[0034] Mica powder, Lingshou Runhui Mineral Products Processing Plant;

[0035] Wollastonite, Jiangxi Aote Technology Co., Ltd.;

[0036] Barium sulfate, Yuncheng Xinzeyuan Chemical Co., Ltd.;

[0037] Antioxidant (model Irganox168, Irganox1010, Irganox1098), BASF.

[0038] The testing instrument used in the present invention is as follows:

[0039] Preparation Example 1

[0040] (1) Weigh 400 g of PP, 160 g of 1,5-naphthalene diisocyanate (NDI), and 1 g of initiator azobisisoheptanenitrile, mix and stir evenly to obtain a mixture;

[0041] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain PP-g-NDI M1.

[0042] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.

[0043] Example 1

[0044] (1) Weigh 90 parts of PP, 10 parts of talc, 0.2 parts of PP-g-NDI M1, and 0.1 parts of Irganox 1010, mix and stir to obtain a mixture;

[0045] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material P1.

[0046] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.

[0047] Comparative Example 1

[0048] (1) Weigh 90 parts of PP, 10 parts of talc, and 0.1 parts of Irganox 1010, mix and stir evenly to obtain a mixture;

[0049] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material D1.

[0050] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.

[0051] Comparative Example 2

[0052] (1) Weigh 90 parts of PP, 10 parts of talc, 0.2 parts of SEBS-g-MAH, and 0.1 parts of Irganox 1010, mix and stir evenly to obtain a mixture;

[0053] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material D2.

[0054] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.

[0055] The PP composite materials prepared in the above Example 1 and Comparative Examples 1-2 were made into test strips using an injection molding machine. The test data are as follows:

[0056] Test items Test Standards unit P1 D1 D2 Tensile Strength ASTM D638 MPa 15.9 11.9 13.2 Bending Strength ASTM D790 MPa 1520 1160 1330 Izod notched impact strength ASTM D256 kJ / m2 4.2 2.2 3.1

[0057] As can be seen from the above table, the composite material prepared in Example 1 has a high grafting rate due to the addition of thermoplastic resin-g-NDI, which maximizes the improvement of the compatibility between the thermoplastic resin and the mineral filler, thereby improving the mechanical properties of the thermoplastic resin, which is significantly better than Comparative Examples 1-2.

[0058] Preparation Example 2

[0059] (1) Weigh 500 g of PBT, 200 g of 1,5-naphthalene diisocyanate (NDI), and 3 g of initiator azobisisobutyronitrile, mix and stir evenly to obtain a mixture;

[0060] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain PBT-g-NDI M2.

[0061] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0062] Example 2

[0063] (1) Weigh 110 parts of PBT, 16 parts of calcium carbonate, 0.4 parts of PBT-g-NDI M2, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1098, mix and stir to obtain a mixture;

[0064] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material P2.

[0065] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0066] Comparative Example 3

[0067] (1) Weigh 110 parts of PBT, 16 parts of calcium carbonate, 0.4 parts of PBT-g-NDI M2, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1098, mix and stir to obtain a mixture;

[0068] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material P2.

[0069] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0070] Comparative Example 4

[0071] (1) Weigh 110 parts of PBT, 16 parts of calcium carbonate, 0.4 parts of SEBS-g-MAH, 0.1 parts of antioxidant Irganox 1010, 0.2 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1098, mix and stir to obtain a mixture;

[0072] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material D2.

[0073] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0074] The PBT composite materials prepared in the above Example 2 and Comparative Examples 3-4 were made into strips by injection molding and tested. The test data are shown in the following table:

[0075] Test items Test Standards unit P2 D3 D4 Tensile Strength ASTM D638 MPa 65.6 58.2 60.3 Bending Strength ASTM D790 MPa 3260 2760 3010 Izod notched impact strength ASTM D256 kJ / m2 5.2 3.3 4.1

[0076] It can be seen from the above table that the mechanical properties of Example 2 are better than those of Comparative Examples 3-4.

[0077] Preparation Example 3

[0078] (1) Weigh 450 g of PE, 180 g of 1,5-naphthalene diisocyanate (NDI), and 2 g of initiator benzoyl peroxide, mix and stir evenly to obtain a mixture;

[0079] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain PE-g-NDI M3.

[0080] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.

[0081] Example 3

[0082] (1) Weigh 100 parts of PE, 13 parts of mica powder, 0.3 parts of PE-g-NDI M3, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010, mix and stir to obtain a mixture;

[0083] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material P3.

[0084] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.

[0085] Comparative Example 5

[0086] (1) Weigh 100 parts of PE, 13 parts of mica powder, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010, mix and stir evenly to obtain a mixture;

[0087] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material D5.

[0088] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.

[0089] Comparative Example 6

[0090] (1) Weigh 100 parts of PE, 13 parts of mica powder, 0.3 parts of SEBS-g-MAH, 0.1 parts of antioxidant Irganox 168, and 0.2 parts of antioxidant Irganox 1010, mix and stir to obtain a mixture;

[0091] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material D6.

[0092] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.

[0093] The PE composite materials prepared in the above Example 3 and Comparative Examples 5-6 were made into test strips by injection molding machine, and the test data are as follows:

[0094] Test items Test Standards unit P3 D5 D6 Tensile Strength ASTM D638 MPa 12.4 9.2 10.1 Bending Strength ASTM D790 MPa 1320 920 1010 Izod notched impact strength ASTM D256 kJ / m2 3.3 1.5 2.2

[0095] It can be seen from the above table that the mechanical properties of Example 3 are better than those of Comparative Examples 5-6.

[0096] Preparation Example 4

[0097] (1) Weigh 425 g of PA6, 185 g of 1,5-naphthalene diisocyanate (NDI), and 2.5 g of initiator azobisisoheptanenitrile, mix and stir evenly to obtain a mixture;

[0098] (2) Extruding the mixture obtained in step (1) from an extruder and granulating it to obtain PA6-g-NDI M4.

[0099] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.

[0100] Example 4

[0101] (1) Weigh 95 parts of PA6, 15 parts of wollastonite, 0.2 parts of PA6-g-NDI M4, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1098, mix and stir evenly to obtain a mixture;

[0102] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material P4.

[0103] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.

[0104] Example 7

[0105] (1) Weigh 95 parts of PA6, 15 parts of wollastonite, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1098, mix and stir evenly to obtain a mixture;

[0106] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material D7.

[0107] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.

[0108] Comparative Example 8

[0109] (1) Weigh 95 parts of PA6, 15 parts of wollastonite, 0.2 parts of SEBS-g-MAH, 0.1 parts of antioxidant Irganox 1010, and 0.2 parts of antioxidant Irganox 1098, mix and stir to obtain a mixture;

[0110] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material D8.

[0111] The twin-screw extruder includes six temperature zones arranged in sequence. The temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, and the temperature of the sixth temperature zone is 260°C. The head temperature of the twin-screw extruder is 260°C and the screw speed is 320r / min.

[0112] The PA6 composite materials prepared in the above Example 4 and Comparative Examples 7-8 were made into strips by injection molding machine for testing. The test data are shown in the following table:

[0113] Test items Test Standards unit P4 D7 D8 Tensile Strength ASTM D638 MPa 74.4 65.8 70.1 Bending Strength ASTM D790 MPa 3270 2640 3020 Izod notched impact strength ASTM D256 kJ / m2 3.9 2.1 2.6

[0114] It can be seen from the above table that the mechanical properties of Example 4 are better than those of Comparative Examples 7-8.

[0115] Preparation Example 5

[0116] (1) Weigh 455 g of PS, 175 g of 1,5-naphthalene diisocyanate (NDI), and 1.5 g of initiator azobisisoheptanenitrile, mix and stir evenly to obtain a mixture;

[0117] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain PS-g-NDI M5.

[0118] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.

[0119] Example 5

[0120] (1) Weigh 105 parts of PS, 14 parts of barium sulfate, 0.35 parts of PS-g-NDI M5, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir to obtain a mixture;

[0121] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material P5.

[0122] The twin-screw extruder includes six temperature zones arranged in sequence, wherein the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.

[0123] Comparative Example 9

[0124] (1) Weigh 105 parts of PS, 14 parts of barium sulfate, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir to obtain a mixture;

[0125] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material D9.

[0126] The twin-screw extruder includes six temperature zones arranged in sequence, wherein the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.

[0127] Comparative Example 10

[0128] (1) Weigh 105 parts of PS, 14 parts of barium sulfate, 0.35 parts of SEBS-g-MAH, 0.1 parts of antioxidant Irganox 1010, and 0.1 parts of antioxidant Irganox 168, mix and stir to obtain a mixture;

[0129] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material D10.

[0130] The twin-screw extruder includes six temperature zones arranged in sequence, wherein the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.

[0131] The PS composite materials prepared in the above Example 5 and Comparative Examples 9-10 were made into strips by injection molding and tested. The test data are shown in the following table:

[0132] Test items Test Standards unit P5 D9 D10 Tensile Strength ASTM D638 MPa 52.3 46.5 49.6 Bending Strength ASTM D790 MPa 4010 3460 3770 Izod notched impact strength ASTM D256 kJ / m2 4.5 2.5 3.2

[0133] It can be seen from the above table that the mechanical properties of Example 5 are better than those of Comparative Examples 9-10.

[0134] This shows that the thermoplastic resin composite material prepared by the method provided by the present invention has excellent mechanical properties and can expand the application field of the thermoplastic resin composite material.

[0135] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0136] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A thermoplastic resin composite material with excellent mechanical properties, characterized in that: It is composed of the following components by weight:

2. The thermoplastic resin composite material according to claim 1, characterized in that: The mineral filler is one of talcum powder, calcium carbonate, mica powder, wollastonite and barium sulfate.

3. The thermoplastic resin composite material according to claim 1, characterized in that: The preparation steps of the thermoplastic resin-g-NDI are as follows: (1) mixing a thermoplastic resin, 1,5-naphthalene diisocyanate and an initiator, and stirring the mixture to obtain a mixture; (2) The mixed material is added into an extruder and granulated by extrusion to obtain a thermoplastic resin - g-NDI.

4. The thermoplastic resin composite material according to claim 3, characterized in that: The initiator is azobisisobutyronitrile, sodium persulfate, benzoyl peroxide or azobisisobutyronitrile.

5. The thermoplastic resin composite material according to claim 3, characterized in that: The mass ratio of the thermoplastic resin, 1,5-naphthalene diisocyanate and the initiator is (40-50):(16-20):(0.1-0.3).

6. The thermoplastic resin composite material according to claim 1 or 3, characterized in that: The thermoplastic resin is one of polyethylene, polypropylene, polystyrene, polybutylene terephthalate and polyamide 6.

7. The thermoplastic resin composite material according to claim 1, characterized in that: The antioxidant is one or a mixture of tris(2,4-di-tert-butyl)phenyl phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and N,N'-hexane-1,6-diylbis(3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide)).

8. The method for preparing a thermoplastic resin composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Weigh 80-100 parts of a thermoplastic resin, 10-16 parts of a mineral filler, 0.2-0.4 parts of a thermoplastic resin-g-NDI, and 0.1-0.5 parts of an antioxidant, mix and stir to obtain a mixture; (2) Extruding the mixed material obtained in step (1) from an extruder and granulating it to obtain a thermoplastic resin composite material.

Citation Information

Patent Citations

  • PP-PS composite material and preparation method thereof

    CN108314858A

  • High filling thermoplastic resin composite material and preparation method thereof

    CN110591223A